2005
DOI: 10.1073/pnas.0508228102
|View full text |Cite
|
Sign up to set email alerts
|

Arp2/3 complex-deficient mouse fibroblasts are viable and have normal leading-edge actin structure and function

Abstract: RNA interference silencing of up to 90% of Arp3 protein expression, a major subunit of the Arp2͞3 complex, proportionately decreases the intracellular motility of Listeria monocytogenes and actin nucleation activity ascribable to the Arp2͞3 complex in mouse embryonic fibroblasts. However, the Arp2͞3-deficient cells exhibit unimpaired lamellipodial actin network structure, translational locomotion, spreading, actin assembly, and ruffling responses. In addition, Arp3-silenced cells expressing neural Wiskott-Aldr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
46
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 32 publications
15
46
0
Order By: Relevance
“…The SCAR/ WAVE complex plays an important role in regulating actin filament arrangement by activating the Arp2/3 complex to modify actin filament organization (Blanchoin et al, 2000;Frank et al, 2004;Beltzner and Pollard, 2008). Mutations in key components of the SCAR/ WAVE-Arp2/3 complex result in various defects in yeast and animals (Winter et al, 1999;Di Nardo et al, 2005). In many cases, these mutations cause embryonic arrest and zygotic lethality by impairing various cellular activities (Severson et al, 2002;Sawa et al, 2003;Vartiainen and Machesky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The SCAR/ WAVE complex plays an important role in regulating actin filament arrangement by activating the Arp2/3 complex to modify actin filament organization (Blanchoin et al, 2000;Frank et al, 2004;Beltzner and Pollard, 2008). Mutations in key components of the SCAR/ WAVE-Arp2/3 complex result in various defects in yeast and animals (Winter et al, 1999;Di Nardo et al, 2005). In many cases, these mutations cause embryonic arrest and zygotic lethality by impairing various cellular activities (Severson et al, 2002;Sawa et al, 2003;Vartiainen and Machesky, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that Arp2/3 is recruited to nascent integrin adhesions (DeMali et al, 2002;Serrels et al, 2007) and that the actin retrograde flow can transfer myosin II-generated tension to promote adhesion growth and maturation (Galbraith et al, 2002;Choi et al, 2008;Wolfenson et al, 2011). Consequently, we propose that Arp2/3 inhibition reduces the chance for adhesions to interact with the overhead actin network because of its reduced branch density, in turn, leading to reduced tension on adhesions by the retrograde flow, which could reduce their maturation and/or stability.…”
Section: Discussionmentioning
confidence: 99%
“…This multiprotein complex binds to the side of a preexisting actin filament and nucleates an actin branch (Mullins et al, 1997). This branched actin network has been implicated in numerous processes in non-neuronal cells (Goley and Welch, 2006), most commonly associated with lamellipodial formation and protrusion (Suraneni et al, 2012;Wu et al, 2012), though not all reports agree (Di Nardo et al, 2005). Arp2/3 is also required for haptotaxis in fibroblasts, but not chemotaxis (Wu et al, 2012); although, other groups have shown it is required for chemotaxis (Mukai et al, 2005;Suraneni et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Reconstituted motility assays also enabled controlled measurements of the force produced by actin polymerization (30). WASP family proteins use Arp2/3 complex to branch filaments at the leading edge, whereas formins may contribute to lamellipodium or filopodium or nerve growth cone extension or even supplement the absence of Arp2/3 (31,32).…”
Section: Insight Into the Mechanism Of Actin-based Motility From Recomentioning
confidence: 99%